Pharmacokinetics of Rilpivirine in HIV-Infected Pregnant Women - Anna H. Tran (2018)
© Copyright 2016 Wolters Kluwer Health, Inc. All rights reserved. Background: Rilpivirine pharmacokinetics is defined by its absorption, distribution, metabolism, and excretion. Pregnancy can affect these factors by changes in cardiac output, protein binding, volume of distribution, and cytochrome P450 (CYP) 3A4 activity. Rilpivirine is metabolized by CYP3A4. The impact of pregnancy on rilpivirine pharmacokinetics is largely unknown. Methods: International Maternal Pediatric Adolescent AIDS Clinical Trials P1026s is a multicenter, nonblinded, prospective study evaluating antiretroviral pharmacokinetics in HIV-infected pregnant women that included a cohort receiving rilpivirine 25 mg once daily as part of their combination antiretrovirals for clinical care. Thirty-two women were enrolled in this study. Intensive pharmacokinetic sampling was performed at steady state during the second trimester, the third trimester, and postpartum. Maternal and umbilical cord blood samples were obtained at delivery. Plasma rilpivirine concentration was measured using liquid chromatography-mass spectrometry; lower limit of quantitation was 10 ng/mL. Results: Median (range) AUC0-24were 1969 (867-4987, n 15), 1669 (556-4312, n 28), and 2387 (188-6736, n 28) ng·h/mL in the second trimester, the third trimester, and postpartum, respectively (P < 0.05 for either trimester vs postpartum). Median (range) C24were 63 (37-225, n 17), 56 (<10-181, n 30), and 81 (<10-299, n 28) ng/mL (P < 0.05 for either trimester vs postpartum). High variability in pharmacokinetic parameters was observed between subjects. Median (range) cord blood/maternal concentration ratio was 0.55 (0.3-0.8, n 21). Delivery HIV-1 RNA was ≤50 copies per milliliter in 70% and ≤400 copies per milliliter in 90% of women. Cminwere significantly lower at 15 visits with detectable HIV-1 RNA compared with 61 visits with undetectable HIV-1 RNA, 29 (<10-93) vs 63 (15-200) ng/mL (P 0.0001). Cminwas below the protein binding-adjusted EC90concentration (12.2 ng/mL) at 4 visits in 3 of 31 women (10%). Conclusions: Rilpivirine exposure is lower during pregnancy compared with postpartum and highly variable. Ninety percent of women had minimum concentrations above the protein binding-adjusted EC90for rilpivirine.